The role of miRNAs in the development of cholangiopathies. Part 1 - A.E. Abaturov; V.L. Babуch (Zaslavsky O.Yu., 2023)
The role of miRNA in the development of cholangiopathies is given in the scientific review. This article discusses the role of miRNA in primary sclerosing cholangitis and primary biliary cholangitis. To write the article, information was searched using Scopus, Web of Science, MedLine, PubMed, Google Scholar, Embase, Global Health, The Cochrane Library databases. The authors state that in hepatobiliary diseases, namely cholangiopathies, micro-RNAs affect the regulation of hepatocyte, cholangiocyte proliferation, cell cycle, inflammatory processes, fibrosis, chemoresistance and cell survival. Researchers have determined that patients with primary sclerosing cholangitis have significantly increased levels of miR-26a, miR-30b, miR-126, miR-122, miR-194, miR-1281 in blood serum and miR-412, miR-640, miR-1537 and miR-3189 in the bile of relatively healthy individuals. It is known that the number of differentially expressed miRNAs in patients with primary biliary cholangitis reaches 97, of which the most diagnostically significant is miR-139-5p. Scientists note that increased miR-139-5p expression in hepatocytes correlates with increased production of TNF-α and repression of c-FOS gene transcription. It is stated that the researchers proposed an alternative hypothesis of miRNA-mediated induction of the inflammatory reaction of the bile ducts in primary biliary cholangitis. The hypothesis is presented that the activity of the generation of miR-106b-5p, miR-20a-5p, and miR-93-5p, which perform key regulatory functions in it, is the basis of the functioning of the miRNA-mRNA network in primary biliary cholangitis. Thus, the data of modern research indicate that cholangiopathies are accompanied by a change in the spectrum of production of various micro-RNAs that regulate the activation of inflammation, regeneration, proliferation, apoptosis of hepatocytes and cholangiocytes. A decrease or increase in the level of some micro-RNA expression is critical in the pathological processes that occur in primary sclerosing cholangitis and primary biliary cholangitis, but micro-RNAs can be not only markers, but also targets of these processes.